1992
DOI: 10.1034/j.1399-3054.1992.850218.x
|View full text |Cite
|
Sign up to set email alerts
|

Root nodule development: origin, function and regulation of nodulin genes

Abstract: M. 1992. Root nodule development: origin, function and regulation of nodulin genes. -Physiol. Plant. 85: 253-265,The symbiotic root nodule, an organ formed on leguminous plants, is a product of successful interactions between the host plant and the soil bacteria, Rhizobium spp. Plant hormones play an important role in the genesis of this organ. The hormonal balance appears to be modulated by the signals produced by bacteria. Many host genes induced during nodule organogenesis and the symbiotic state have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…lnduced polypeptides are most frequent and can represent -4% of resolved polypeptides (DumasGaudot et al, 1994b;Samra et al, 1996). Although such mycorrhiza-induced polypeptides have been called mycorrhizins, in analogy to nodulins, actinorhizins, and haustorins in other plant-microbe interactions (verma et al, 1992;Roberts et al, 1993;Seguin and Lalonde, 1993), those of plant origin have not been conclusively identified. Mycorrhiza-resistant pea mutants respond differently when challenged with an AM fungus, the major modification being the disappearance of polypeptides normally present in uninoculated plants (Samra et al, 1996).…”
Section: Mycorrhiza-specific Molecular Responsesmentioning
confidence: 99%
“…lnduced polypeptides are most frequent and can represent -4% of resolved polypeptides (DumasGaudot et al, 1994b;Samra et al, 1996). Although such mycorrhiza-induced polypeptides have been called mycorrhizins, in analogy to nodulins, actinorhizins, and haustorins in other plant-microbe interactions (verma et al, 1992;Roberts et al, 1993;Seguin and Lalonde, 1993), those of plant origin have not been conclusively identified. Mycorrhiza-resistant pea mutants respond differently when challenged with an AM fungus, the major modification being the disappearance of polypeptides normally present in uninoculated plants (Samra et al, 1996).…”
Section: Mycorrhiza-specific Molecular Responsesmentioning
confidence: 99%
“…Most of the late nodulins are expressed at the same time or slightly after the induction of the Lb genes (see references in Verma et al, 1992).…”
Section: Indeterminate Nodulesmentioning
confidence: 99%
“…These studies have shown that mycorrhizal colonization of the root system results in the appearance of new proteins, increases the production of some polypeptides already present in uninfected roots and\or decreases the amount of others. The newly induced polypeptides, of plant or fungal origin, have been called endomycorrhizins by analogy to nodulins (Verma, Hu & Zhang, 1992), ectomycorrhizins (Hilbert & Martin, 1988), and haustorins (Roberts et al, 1993), produced in other plant-microbe interactions. However, the origin and role of these endomycorrhizins have not yet been determined, although some of them could be similar to certain nodulins induced during the Rhizobium-legume symbiosis (van Rhijn et al, 1997).…”
Section: mentioning
confidence: 99%